Sintered copper paste for TSV hole filling and preparation method and filling method thereof

By using sintered copper paste composed of copper particles, surfactants and solvents, combined with printing and sintering processes, the problems of voids and thermal mechanical stress in TSV hole filling are solved, and low-cost and efficient green filling is achieved, satisfying the conductive and Thermal conductivity requirements.

CN119114934APending Publication Date: 2024-12-13SHENZHEN XINYUAN NEW MATERIALS CO LTD

Patent Information

Application Number
CN202411264951.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-10
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The traditional TSV pore filling technology has problems such as cutting-edge effects that easily form hollows, easily generate thermal mechanical stress, and high costs. There is a limitation on the size effect of nano-copper particles when sintered at low temperatures.

Method used

Sintered copper paste consisting of 50%-95% copper particles, 0.01%-5% surfactant and 5%-50% solvent, and through printing, pre-drying and sintering steps under vacuum conditions of 150-300°C. Filling to form a dense sintering network to avoid hollows and thermal mechanical stresses and reduce costs.

Benefits of technology

Fast and efficient green filling is achieved, avoiding the formation of voids when filling high aspect ratio holes, reducing filling costs, providing excellent electrical and thermal conductivity, and alleviating thermal stress.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119114934A_ABST
    Figure CN119114934A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of integrated circuits, electronic packaging, printing materials, processes and the like, and provides sintered copper paste for TSV hole filling and a preparation method and a filling method thereof.The sintered copper paste comprises, by weight, 50%-95% of copper particles, 1%-5% of a surfactant and 1%-5% of a solvent. The weight ratio of the surfactant in the sintered copper paste is 0.01%-5%, and the weight ratio of the solvent in the sintered copper paste is 5%-50%. The sintered copper paste is used for TSV hole filling, and can avoid the formation of holes during high aspect ratio hole filling, relieve thermal mechanical stress, reduce filling cost and realize rapid and efficient green filling.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical fields of integrated circuits, electronic packaging, printing materials and processes, and in particular to a sintered copper paste for TSV hole filling and a preparation method and a filling method thereof. Background Art

[0002] Electronic packaging technology provides electrical connections, mechanical support and protection for semiconductor devices working under certain conditions. When semiconductor device technology develops to the nanoscale, traditional two-dimensional packaging technology can no longer meet the requirements of miniaturization, high power, low power consumption, high reliability and multifunctionality of large-scale integrated circuits. Therefore, 3D system-level packaging technology was born and developed rapidly. TSV refers to the manufacture of through holes in silicon, filling conductors, and realizing vertical interconnection based on silicon dielectrics. It is one of the key technologies for manufacturing 3D integrated circuits with good performance. TSV can realize vertical interconnection between chips, effectively shorten the interconnection length, reduce signal transmission delay and loss, and improve signal quality. Traditional TSV hole filling is completed by electroplating copper process. Due to the tip effect of the electroplating process, voids are easily formed when filling high aspect ratio holes. In addition, the thermal expansion coefficients of copper and silicon are quite different, which is easy to generate thermomechanical stress, leading to device failure. Moreover, the electroplating copper process will produce an over-plated copper layer on the silicon surface, which requires expensive chemical mechanical polishing process for treatment, which increases the cost of TSV hole filling.

[0003] In summary, the existing TSV hole filling technology has technical problems such as the tip effect that easily forms voids, easily generates thermomechanical stress, and has high costs. However, due to the size effect, nano copper particles have small metal particle size, large specific surface area, and high surface free energy. Atomic diffusion can occur between 200-300°C to achieve sintering, and the sintered body after cooling and solidification has mechanical, electrical and thermal properties close to those of bulk copper, so low-temperature sintering and high-temperature service can be achieved. In the TSV hole filling process, due to the temperature limit of the wafer carrier system bonding layer, the filling process must be carried out in an environment below this limit temperature, usually below 250°C, while the operating temperature of the chip often exceeds 300°C. Therefore, the characteristics of low-temperature sintering and high-temperature service of sintered copper paste meet the TSV hole filling requirements, and also have the advantages of excellent performance, low cost and green environmental protection. Summary of the invention

[0004] In order to solve the problems in the prior art, the present invention provides a sintered copper paste for TSV hole filling and a preparation method and a filling method thereof, so as to be used for TSV hole filling, avoid the formation of voids when filling high aspect ratio holes, relieve thermomechanical stress, reduce filling costs, and achieve fast, efficient and green filling.

[0005] In a first aspect, the present invention provides a sintered copper paste for TSV hole filling, comprising:

[0006] Copper particles, wherein the weight ratio of the copper particles in the sintered copper paste is 50%-95%;

[0007] A surfactant, wherein the weight ratio of the surfactant in the sintered copper paste is 0.01%-5%;

[0008] The solvent accounts for 5% to 50% by weight of the solvent in the sintered copper paste.

[0009] Furthermore, the metal-based purity of the copper particles is ≥80%.

[0010] Furthermore, the copper particles have a particle size of 10 nm to 10 μm.

[0011] Furthermore, the copper particles have a coating layer on their surfaces, and the coating layer comprises any one or more of polyvinyl pyrrolidone, citric acid, sodium citrate, ascorbic acid, ethylenediamine, hexadecyltrimethylammonium bromide, phenylacetic acid, sodium dodecylsulfonate, glucose, sodium metaphosphate, and pectin. The coating layer helps to improve the dispersibility and oxidation resistance of the copper particles in the copper paste and improve the sintering quality.

[0012] Furthermore, the surfactant includes any one or more of Dyno l 604 non-ionic surfactant, FS-3100 fluorinated non-ionic surfactant, alkylphenol polyoxyethylene ether, stearic acid glycerol, fatty alcohol polyoxyethylene ether, tetrahydroxypropyl ethylenediamine, and fatty acid methyl ester polyoxyethylene ether. Adding the surfactant helps to improve the wettability of copper particles in the copper paste, thereby increasing the solid content of the copper paste and further improving the density of the sintered body.

[0013] Furthermore, the solvent includes any one or more of ethylene glycol, diethylene glycol, propylene glycol, and terpineol. The solvent is used to dissolve the surfactant, and the viscosity and solid content of the copper paste can be adjusted by adjusting the solvent content.

[0014] In a second aspect, the present invention provides a method for preparing a sintered copper paste for TSV hole filling, comprising:

[0015] Mix and dissolve the surfactant and the solvent to obtain solution A;

[0016] The copper particles with a coating layer on the surface are mixed with solution A and stirred to obtain a sintered copper paste.

[0017] Furthermore, the surfactant includes any one or more of Dyno l 604 non-ionic surfactant, FS-3100 fluorine-containing non-ionic surfactant, alkylphenol polyoxyethylene ether, stearic acid glyceryl ester, fatty alcohol polyoxyethylene ether, tetrahydroxypropyl ethylenediamine, and fatty acid methyl ester polyoxyethylene ether, and the weight ratio of the surfactant in the sintered copper paste is 0.01%-5%; the solvent includes any one or more of ethylene glycol, diethylene glycol, glycerol, and terpineol, and the weight ratio of the solvent in the sintered copper paste is 5%-30%; the weight ratio of the copper particles in the sintered copper paste is 70%-95%.

[0018] Furthermore, the metal-based purity of the copper particles is ≥80%.

[0019] Furthermore, the copper particles have a particle size of 10 nm to 10 μm.

[0020] Furthermore, the copper particles have a coating layer on their surfaces, and the coating layer comprises any one or more of polyvinyl pyrrolidone, citric acid, sodium citrate, ascorbic acid, ethylenediamine, hexadecyltrimethylammonium bromide, phenylacetic acid, sodium dodecylsulfonate, glucose, sodium metaphosphate, and pectin.

[0021] In a third aspect, the present invention provides a method for filling a sintered copper paste for TSV hole filling, comprising:

[0022] Printing: After the insulating layer is deposited on the TSV hole wall, copper paste is printed for filling;

[0023] Pre-drying: Pre-drying is carried out under vacuum conditions at 40-150°C, assisted by centrifugation, for 1-30 minutes;

[0024] Sintering: Sintering is performed under vacuum conditions at 150-300°C for 2-60 minutes to form a dense sintered network, and then cooled to room temperature;

[0025] Furthermore, in the pre-drying step, the centrifugal speed is 200 r / min to 8000 r / min.

[0026] Repeat the above steps of printing, pre-baking and sintering to fill the entire TSV hole with sintered copper paste.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] The present invention provides a sintered copper paste for TSV hole filling, a preparation method thereof, and a filling method, which can avoid the formation of voids when filling high aspect ratio holes, relieve thermomechanical stress, reduce filling costs, and are very environmentally friendly, achieving fast and efficient green filling. Compared with electroplating, the present invention is green and environmentally friendly. On the one hand, high aspect ratio holes can be quickly and efficiently filled completely by centrifugation to avoid the generation of voids, and the copper covering layer on the silicon surface is almost non-existent, thereby eliminating the expensive chemical mechanical polishing process and reducing the filling cost. On the other hand, the copper sintered body is a dense network structure, which reduces the overall Young's modulus of the sintered body, provides deformation space, can alleviate the thermomechanical stress between copper and silicon during service to a certain extent, and has excellent electrical and thermal conductivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] The drawings described herein are used to provide a further understanding of the present invention and constitute a part of the present invention. The exemplary embodiments of the present invention and their description are used to explain the present invention and do not constitute an improper limitation of the present invention. Some specific embodiments of the present invention will be described in detail in an exemplary and non-restrictive manner with reference to the drawings. The same reference numerals in the drawings indicate the same or similar components or parts. It should be understood by those skilled in the art that these drawings are not necessarily drawn to scale. In the drawings:

[0030] Figure 1 1 is a schematic diagram of a component ratio of a sintered copper paste for TSV hole filling according to an embodiment of the present invention;

[0031] Figure 2 It is a schematic flow chart of a method for preparing a sintered copper paste for TSV hole filling according to an embodiment of the present invention;

[0032] Figure 3 It is a schematic flow chart of a filling method of sintered copper paste for TSV hole filling according to an embodiment of the present invention;

[0033] Figure 4 It is a schematic diagram of the effect of a filling method of sintered copper paste for TSV hole filling according to an embodiment of the present invention. DETAILED DESCRIPTION

[0034] The preferred embodiments of the present invention are further described in detail below. It should be noted that the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict. The present invention is further described below in conjunction with the accompanying drawings and specific implementation methods.

[0035] Embodiment 1

[0036] See also Figure 1This embodiment provides a sintered copper paste for TSV hole filling, including copper particles, a surfactant and a solvent, the weight ratio of the copper particles in the sintered copper paste is 50%-95%, the weight ratio of the surfactant in the sintered copper paste is 0.01%-5%, the weight ratio of the solvent in the sintered copper paste is 5%-50%, and the total weight ratio of the three components is 100%.

[0037] It should be noted that the metal base purity of the copper particles is ≥80%, the particle size of the copper particles is 10nm~10μm, and there is a coating layer on the surface of the copper particles, which helps to improve the dispersibility and oxidation resistance of the copper particles in the copper paste. In some preferred embodiments, the weight ratio of the copper particles in the sintered copper paste is 85%, the surfactant is FS-3100 fluorinated non-ionic surfactant, and the weight ratio in the sintered copper paste is 0.5%, and the solvent is propylene glycol, and the weight ratio in the sintered copper paste is 14.5%. The surfactant helps to improve the wettability of the copper particles in the copper paste, thereby increasing the solid content of the copper paste and the density of the sintered body. The solvent is used to dissolve the surfactant, and the viscosity and solid content of the copper paste can be adjusted by adjusting the solvent content.

[0038] It should also be noted that the average particle size of the copper particles is 400 nm, the size distribution is concentrated, D10 / D50 is 0.1, and D90 / D50 is 1.9. The copper particles have a coating layer on the surface, the coating layer is composed of hexadecyltrimethylammonium bromide, and the coating layer helps to improve the dispersibility and oxidation resistance of the copper particles in the copper paste.

[0039] It should also be noted that the sintered copper paste in this embodiment has the following properties: the copper paste sintering temperature is ≤240°C, the sintered body resistivity of the copper paste is ≤20μΩ·cm, the thermal conductivity is ≥100W / (m·K), and it can withstand 1000 thermal cycles at -55°C to 200°C, meeting the TSV hole filling requirements.

[0040] Embodiment 2

[0041] This embodiment provides another sintered copper paste for TSV hole filling, including copper particles, a surfactant and a solvent, wherein the weight ratio of the copper particles in the sintered copper paste is 88%, the surfactant is alkylphenol polyoxyethylene ether, and the weight ratio of the surfactant in the sintered copper paste is 0.5%, and the solvent is pine alcohol, and the weight ratio of the solvent in the sintered copper paste is 11.5%.

[0042] It should be noted that the metal base purity of the copper particles is 90%, that is, the weight ratio of copper in the particles is 90%, and the weight ratio of silver in the particles is 10%, and it has a copper-silver core-shell structure, with copper inside the particles and silver wrapped in the outer layer of the particles. The core-shell structure helps to prevent the particles from being oxidized and improve the sintering performance.

[0043] It should also be noted that the copper particle size is 300nm, and the size distribution is concentrated, D10 / D50 is 0.1, and D90 / D50 is 1.9. The copper particles have a coating layer on the surface, and the coating layer is composed of hexadecyltrimethylammonium bromide, which helps to improve the dispersibility and oxidation resistance of the copper particles in the copper paste.

[0044] It should also be noted that the sintered copper paste in this embodiment is suitable for filling TSV holes with a critical diameter of ≥1.5μm, and has the following properties: pre-drying at 85°C vacuum conditions for 10 minutes, assisted by centrifugation at 4000r / min, sintering can be achieved at 230°C vacuum conditions, and after 15 minutes of complete sintering, the resistivity of the sintered body is 15μΩ·cm, the thermal conductivity is 170W / (m·K), and it can withstand 1000 thermal cycles at -55°C to 200°C, meeting the TSV hole filling requirements. Example 3

[0045] See also Figure 2 This embodiment provides a method for preparing a sintered copper paste for TSV hole filling, comprising the following steps:

[0046] S101, taking Dyno l 604 nonionic surfactant and solvent pineneol in a weight ratio of 0.5%:10% and dissolving them to obtain solution A;

[0047] S102, taking copper particles with ascorbic acid as the surface coating layer and solution A in a weight ratio of 89.5%:10.5%, mixing and stirring evenly to obtain a sintered copper paste. The weight ratio of the components of the obtained sintered copper paste is 89.5% of copper particles, 10% of pine alcohol, and 40.5% of Dyno l 604.

[0048] It should be noted that the particle size of the copper particles is bimodal distribution, the size is recorded as Dn, n is 1 or 2, wherein D1 is 200nm, D2 is 2μm, and the size distribution is concentrated, Dn10 / Dn50 is 0.1, and Dn90 / Dn50 is 1.9. The use of bimodal distribution of copper particles can increase the density of the copper paste sintered body, thereby improving the electrical and thermal conductivity.

[0049] It should also be noted that the sintered copper paste prepared by the preparation method in this embodiment is suitable for TSV hole filling with a critical diameter of ≥10μm. The sintered copper paste prepared by the preparation method in this embodiment is pre-dried for 5 minutes under vacuum conditions at 80°C, assisted by centrifugation at 4000r / min, and can be sintered under vacuum conditions at 220°C. After being completely sintered for 15 minutes, the resistivity of the sintered body is 10μΩ·cm, the thermal conductivity is 200W / (m·K), and it can withstand 1000 thermal cycles at -55°C to 200°C, meeting the TSV hole filling requirements.

[0050] Embodiment 4

[0051] See also Figure 3 This embodiment provides a method for filling a sintered copper paste for TSV hole filling, comprising the following steps:

[0052] S201, printing: after the insulating layer is deposited on the TSV hole wall, copper paste is printed for filling;

[0053] S202, pre-drying: pre-drying under vacuum conditions at 80°C, assisted by centrifugation, with a speed of 5000r / min, for 10min;

[0054] S203, sintering: sintering at 220°C under vacuum conditions for 20 minutes to form a dense sintered network, and then cooling to room temperature;

[0055] Repeat the above steps of S201, printing, S202, pre-drying and S203, sintering, so that the sintered copper paste fills the entire TSV hole.

[0056] It should be noted that the sintered copper paste fills the entire TSV silicon hole to form a dense copper sintered body. The outside of the copper sintered body is the insulation layer of the TSV hole, and the outside of the insulation layer of the TSV hole is silicon. The filling effect is shown in Figure 4 .

[0057] It should also be noted that the role of pre-drying is to volatilize most of the solvent first, which will cause the copper paste to shrink in volume, while the role of centrifugation is to ensure that the copper paste at the bottom of the hole is densely filled after the solvent evaporates and the paste shrinks in volume. In addition, due to the volume shrinkage during drying and sintering, the sintered body will be filled below the hole opening, and multiple printings and the above steps need to be repeated to fill the entire hole with the copper sintered body to avoid the formation of internal voids.

[0058] It should also be noted that sintered copper paste is used for TSV hole filling. Its copper sintered body has a dense network structure, which can reduce the Young's modulus of the sintered structure, provide deformation space, and to a certain extent alleviate the thermomechanical stress between copper and silicon during service, thus meeting the TSV hole filling requirements.

[0059] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A sintered copper paste for TSV hole filling, characterized in that: include: Copper particles, wherein the weight ratio of the copper particles in the sintered copper paste is 50%-95%; A surfactant, wherein the weight ratio of the surfactant in the sintered copper paste is 0.01%-5%; The solvent accounts for 5% to 50% by weight of the solvent in the sintered copper paste.

2. The sintered copper paste for TSV hole filling according to claim 1, characterized in that: The metal base purity of the copper particles is ≥80%; the particle size of the copper particles is 10nm-10μm.

3. The sintered copper paste for TSV hole filling according to claim 1, characterized in that: The copper particles have a coating layer on their surfaces, and the coating layer comprises any one or more of polyvinyl pyrrolidone, citric acid, sodium citrate, ascorbic acid, ethylenediamine, hexadecyltrimethylammonium bromide, phenylacetic acid, sodium dodecylsulfonate, glucose, sodium metaphosphate, and pectin.

4. The sintered copper paste for TSV hole filling according to claim 1, characterized in that: The surfactant includes any one or more of Dynol 604 nonionic surfactant, FS-3100 fluorine-containing nonionic surfactant, alkylphenol polyoxyethylene ether, stearic acid glyceryl ester, fatty alcohol polyoxyethylene ether, tetrahydroxypropyl ethylenediamine, and fatty acid methyl ester polyoxyethylene ether; the solvent includes any one or more of ethylene glycol, diethylene glycol, glycerol, and terpineol.

5. A method for preparing a sintered copper paste for TSV hole filling, characterized in that: include: Mix and dissolve the surfactant and the solvent to obtain solution A; The copper particles with a coating layer on the surface are mixed with solution A and stirred to obtain a sintered copper paste.

6. The method for preparing a sintered copper paste for TSV hole filling according to claim 5, characterized in that: The weight ratio of the copper particles in the sintered copper paste is 50%-95%; the surfactant includes any one or more of Dynol 604 non-ionic surfactant, FS-3100 fluorine-containing non-ionic surfactant, alkylphenol polyoxyethylene ether, stearic acid glycerol, fatty alcohol polyoxyethylene ether, tetrahydroxypropyl ethylenediamine, and fatty acid methyl ester polyoxyethylene ether, and the weight ratio in the sintered copper paste is 0.01%-5%; the solvent includes any one or more of ethylene glycol, diethylene glycol, glycerol, and terpineol, and the weight ratio in the sintered copper paste is 5%-50%, and the total weight ratio of the three components is 100%.

7. The method for preparing a sintered copper paste for TSV hole filling according to claim 5, characterized in that: The copper particles have a metal base purity of ≥80% and a particle size of 10 nm to 10 μm.

8. The method for preparing a sintered copper paste for TSV hole filling according to claim 5, characterized in that: The coating layer on the surface of the copper particles comprises any one or more of polyvinyl pyrrolidone, citric acid, sodium citrate, ascorbic acid, ethylenediamine, hexadecyltrimethylammonium bromide, phenylacetic acid, sodium dodecylsulfonate, glucose, sodium metaphosphate and pectin.

9. A method for filling a sintered copper paste for TSV hole filling, characterized in that: include: Printing: After the insulating layer is deposited on the TSV hole wall, copper paste is printed for filling; Pre-drying: Pre-drying is carried out under vacuum conditions at 40-150°C, assisted by centrifugation, for 1-30 minutes; Sintering: Sintering is performed under vacuum conditions at 150-300°C for 2-60 minutes to form a dense sintered network, and then cooled to room temperature; Repeat the above steps of printing, pre-baking and sintering to fill the entire TSV hole with sintered copper paste.

10. The method for filling a sintered copper paste for TSV hole filling according to claim 9, characterized in that: In the pre-drying step, the centrifugal speed is 200 r / min to 8000 r / min.

Citation Information

Patent Citations

  • Wafer processing laminate, temporary adhesive material for wafer processing, and method for manufacturing thin wafer

    CN105733498A

  • Method for producing substrate having through-silicon vias, substrate having through-silicon vias, and copper paste for through-silicon via formation

    CN113711337A

  • Interconnection structure manufacturing method based on metal powder filling

    CN117374004A

  • Coated copper particle, method for manufacturing coated copper particle, copper paste, method for manufacturing copper paste, and semiconductor device

    JP2022026615A

Cited By

  • Self-filling method for high-aspect-ratio micropores of substrate

    CN120048740A